Rents from power for a dissident elite and mass mobilization. (6th December 2018) - Aköz, Kemal Kivanç; Hernández‐Lagos, Pablo
Abstract: Popular uprisings in autocracies seldom lead to democratic regimes. We propose a model that helps explain how rents from power encourage popular revolts. We study why citizens would follow a dissident group seeking regime change, if rents from change accrue only to the group. Our model predicts that higher rents may increase the incidence of public mobilization because rents facilitate coordination. The results suggest that cohesive dissident groups may spur seemingly spontaneous mass mobilizations, even when the mass public know that the dissident group is driven by greed rather than a genuine desire to halt incumbent's rent‐seeking activities.